Analysis of Lut Tawar Health Center Service Quality on Outpatient Patient Satisfaction in Central Aceh Regency - Amirah, Asriwati; Nyorong, Mappeaty; Nananda, Wahyu Fatrah (International Journal Papier Advance and Scientific Review, 2021)
The purpose of this study was to find out what aspects were related to the quality of service at the Lut Tawar Health Center to the Satisfaction of Outpatients in Central Aceh Regency. The research design used in this study was Cross Sectional. The population in this study was 7,507 people and the samples taken by accidental sampling were 99 people. Data collection methods are primary data and secondary data. Analysis of the data used is a binary logistic regression test. The results showed that the physical condition had a sig-p value of 0.004 < 0.05, reliability sig-p 0.004 < 0.005, and a sig-p guarantee of 0.030 < 0.05, which means that it has a relationship with the quality of health services, while responsiveness has no relationship to the quality of health services because it has a sig-p value of 0.173 > 0.05 and concern has no relationship to the quality of health services because it has a sig-p value of 0.893 > 0.05. The most dominant aspect related to service quality is the variable of physical condition p = 0.004 <0.05. The conclusion in this study is that there is a relationship between physical condition, reliability, and assurance on the quality of Community Health Center (puskesmas) services, while the responsiveness and caring variables have no relationship to the quality of puskesmas services.